Mechanism of Action for rTMS: A Working Hypothesis Based on Animal Studies - Soundara Rajan, Thangavelu; Ghilardi, Maria F. M.; Wang, Hoau-Yan; Mazzon, Emanuela; Bramanti, Placido; Restivo, Domenico; Quartarone, Angelo (Frontiers in Physiology, 2017)
Experiments in rodents have elucidated some of the molecular mechanisms underlying repetitive transcranial magnetic stimulation (rTMS). These studies may be useful in a translational perspective so that future TMS studies in rodents can closely match human TMS protocols designed for therapeutic purposes. In the present work we will review the effects of rTMS on glutamate neurotransmission which in turn induce persistent changes in synaptic activity. In particular we will focus on the role of NMDA and non- NMDA transmission and on the permissive role of BDNF-TrKB interaction in the rTMS induced after-effects.